CONTINUOUS CONTOUR TRENCHING TECHNOLOGY FOR WATERSHED DEVELOPMENT PROGRAM - Sadgir, P.A.; Takalkar, V.G. (Journal of Soil and Water Conservation, 2022)
Watershed management is the need of the hour not only for soil conservation. ground water conservation but it also had impact on national economy and solution for employment problem. For balancing of the balance of the VASUNDHARA, it is necessary to maintain atleast 33 per cent forest coverage of the available land in each country. This CCT method reduces soil erosion to minimum level and the plant growth on such trenches is very promising with 90 per cent survival rate with increase in height of plant from 45 cm basic height to 2m within only 6 months. This method can be adopted in low rainfall area to high rainfall area and from flat area to hilly area with 65 per cent steep slope. This method is suitable for plantation of all species and easy; simple for labourers and comparatively less record keeping. The advantage is that the method is easy and detail checking is possible at a glance. In Ahmadnagar district of Maharashtra state (INDIA) within last four years 17,810 hectares forest area is covered with this CCT method. The case study of DOLASANE is discussed in the paper is of the CCT work carried out in the forest area. All the details about the watershed management work and its effect on socio-economic aspect has been discussed in this paper.